2016
DOI: 10.1080/09638288.2016.1189606
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation of the World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) for Hebrew-speaking subjects with and without hand injury

Abstract: The results support the reliability and validity of this Hebrew translation of the 12-item WHODAS 2.0. IMPLICATIONS FOR REHABILITATION Measurement tools that assess activities and participation after HI are an essential part of the rehabilitation process. The 12-item WHODAS 2.0 is a useful tool, since it addresses a broader range of activity and participation domains compared to the DASH and enables better implementation of the ICF model. Since the WHODAS 2.0 does not target a specific disease (as oppose to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
5
15
0
Order By: Relevance
“…Younus et al also confirmed the very good repeatability of the 12-item WHODAS 2.0 [ 34 ], and likewise, good consistency over time (1 week) was also affirmed by Moreira et al, who used the test–retest method and obtained an ICC of 0.77 [ 37 ]. Similar test–retest values (ICC value of 0.88) were obtained by Marom et al [ 38 ].…”
Section: Discussionsupporting
confidence: 87%
“…Younus et al also confirmed the very good repeatability of the 12-item WHODAS 2.0 [ 34 ], and likewise, good consistency over time (1 week) was also affirmed by Moreira et al, who used the test–retest method and obtained an ICC of 0.77 [ 37 ]. Similar test–retest values (ICC value of 0.88) were obtained by Marom et al [ 38 ].…”
Section: Discussionsupporting
confidence: 87%
“…The WHODAS 2.0 has been used in the evaluation of disability caused by many conditions such as stroke, hand conditions, dementia, maternal complications, and psychiatric disorders . Regarding women's health, publications using ICF as a reference for functioning and disability are concentrated in oncology and maternal areas .…”
Section: Introductionmentioning
confidence: 99%
“…18 The World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) is a generic instrument that evaluates the difficulties that a person has experienced in social participation and daily activities in the last 30 days, and can be used in general population or groups with specific health conditions. 19 The WHODAS 2.0 has been used in the evaluation of disability caused by many conditions such as stroke, 20 hand conditions, 21 dementia, 22 maternal complications, 23 and psychiatric disorders. 24 Regarding women's health, publications using ICF as a reference for functioning and disability are concentrated in oncology [25][26][27][28][29] and maternal areas.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) short form (Üstün, Kostanjsek, Chatterji, & Rehm, ) is a 12‐item self‐report instrument that was used to assess each participant's domains of functioning associated with a health condition caused by the injury that led to hospitalization, including cognition, mobility, self‐care, getting along with other people, life activities, and participation in community activities. The instrument has been used to measure disability among general populations in many LMICs, including Kenya (Gomez‐Olive et al., ) as well as in populations with various medical conditions (Bachani et al., ; Hanass‐Hancock, Myezwa, & Carpenter, ; Marom, Carel, Sharabi, & Ratzon, ). Evaluation of the WHODAS 2.0's psychometric properties across multiple LMICs has supported measurement invariance and the unidimensional property of the scale (Sousa et al., ).…”
Section: Methodsmentioning
confidence: 99%